Functional Form for Estimating the Lorenz Curve - Bidabad, Bijan; Bidabad, Behrouz (American Finance & Banking Review, 2019)
A flexible Lorenz curve which offers different curvatures allowed by the theory of income distribution is introduced. The intrinsically autoregressive nature of the errors in cumulative data of the Lorenz curve is also under consideration.